Action and function of Chromobacterium violaceum in health and disease: Violacein as a promising metabolite to counteract gastroenterological diseases. Issue 6 (December 2017) - Justo, Giselle Zenker; Durán, Nelson
Abstract: Chromobacterium violaceum is a Gram negative, β-proteobacterium found in the microbiota of tropical and subtropical environments. Although considered an opportunistic pathogen, infection rapidly progress to fatal sepsis, with metastatic abscesses. It is noteworthy the multidrug resistant phenotype of C. violaceum and the possibility of relapse. Recently, an influence of global climate in the incidence of cases beyond the previous areas has been observed. Furthermore, chronic granulomatous disease has been considered a risk factor to infection. Despite the increase in C. violaceum infection incidence and high mortality, most clinicians are not familiar with it. This review pointed out important features of this life threatening microorganism, including its pathogenicity, mechanistic aspects, genetic and drug resistance associated factors, and the clinical association with chronic granulomatous disease. In addition, its main metabolite violacein may be a promising agent to counteract gastroenterological diseases, such as colorectal cancer and inflammatory gastric lesions.